OP0168 Clinical response, drug survival and predictors thereof in 432 patients with ankylosing spondylitis switching anti tumor necrosis factor α therapy: Results from the danish nationwide danbio registry. (23rd January 2014) - Glintborg, B.; Østergaard, M.; Krogh, N.; Tarp, U.; Loft, A.; Hansen, A.; Schlemmer, A.; Fana, V.; Kristensen, M.; Lindegaard, H.; Nordin, H.; Rasmussen, C.; et al.
Abstract : Background: Data on switching of biological treatment in patients with ankylosing spondylitis (AS) are limited. The Danish nationwide DANBIO registry now includes up to ten years of prospective follow up of patients with inflammatory arthritis treated with biologicals in routine care. Objectives: To investigate reasons for switching, treatment response and drug adherence in patients with AS who switch tumor-necrosis-factor-alpha inhibitor (TNFi) treatment in routine clinical care. Methods: AS patients treated with TNFi were identified in DANBIO. Disease activity, clinical response (50% or 20mm reduction in Bath AS Disease Activity Index, BASDAI), drug survival and predictors thereof were studied among patients receiving ≥2 different biological drugs. Results: 1, 436 AS patients (380 women, age 41 (33-50) years (median (IQR))) were identified. Among these, 432 patients (30%) switched to a second and 137 (10%) to a third biological drug during follow-up. Median (IQR) follow-up time was 2.6 (1.1-4.8) years. Switchers were more frequently women, had shorter disease duration and higher BASDAI, Functional Index (BASFI) and visual-analogue-scale (VAS) scores (global, pain, fatigue) compared to non-switchers when starting the first TNFi. The main reason for switching was lack of response (56% of switches from first to second TNFi). BAS- and VAS scores decreased significantly after 6 months' treatment during the first, second and third treatment course. BASDAI scores at baseline vs. 6 months' treatment were 56 (38-73) mm (median (IQR)) vs. 33 (16-59) mm (p=0.001) during the second treatment course and 64 (48-79) mm vs. 52 (28-63) mm (p=0.001) during the third. Median drug survival of the first, second and third TNFi was 3.1, 1.6 and 1.8 years respectively (p<0.001). After ∼2-years' biological treatment, 52% of switchers and 63% of non-switchers (p=0.01) had achieved response (number needed to treat, NNT=1.9 and 1.6, respectively). Adherence was similar regardless of the reason for switching. Male gender and low BASFI predicted adherence to the second TNFi. Conclusions: Nearly one third of AS patients in clinical practice switched biological treatment. The response rates and drug adherences were lower among switchers, however, half of switchers achieved clinical response. Male gender and low BASFI predicted response to the second TNFi. Irrespective of the reason for discontinuation of the first TNFi, switching to another TNFi should be considered. References: Predictors of treatment response and drug continuation in 842 patients with ankylosing spondylitis treated with anti-tumour necrosis factor: results from 8 years' surveillance in the Danish nationwide DANBIO registry. Glintborg B, Ostergaard M, Krogh NS, Dreyer L, Kristensen HL, Hetland ML. Ann Rheum Dis. 2010 Nov;69(11):2002-8. Disclosure of Interest: B. Glintborg: None Declared, M. Østergaard Speakers Bureau: Abbott, Amgen, Bristol-Meyers Squibb, Centocor, Genmab, GlaxoSmithKline, Novo, Wyeth/Pfizer, Roche, Schering-Plough/MSD and UCB (less than $10, 000 each), N. Krogh: None Declared, U. Tarp: None Declared, A. Loft Consultant for: Schering-Plough/MSD, UCB, Wyeth/Pfizer og Abbott, Speakers Bureau: Schering-Plough/MSD, UCB, Wyeth/Pfizer og Abbott, A. Hansen: None Declared, A. Schlemmer Speakers Bureau: MSD, Roche, V. Fana: None Declared, M. Kristensen: None Declared, H. Lindegaard Consultant for: Roche, H. Nordin: None Declared, C. Rasmussen Grant/Research support from: Wyeth/Pfizer, Abbott, Roche, L. Ejstrup: None Declared, P. Petersen: None Declared, N. Manilo: None Declared, D. Jensen: None Declared, M. Hetland Grant/Research support from: On behalf of DANBIO grants from Abbott, Bristol-Meyers Squibb, Roche, Schering-Plough/MSD, UCB-Nordic, and Wyeth/Pfizer (more than $10, 000 each), Speakers Bureau: Abbott, Centocor, Roche, Schering-Plough/MSD, UCB-Nordic, and Wyeth/Pfizer (less than $10, 000 each)